an Analysis of Experiential Meaning in Poetry “William Wordsworth" - Emeliya Sukma Dara Damanik (Loquen, 2017)
This paper analyzes experiential meaning in poetry written by William Wordsworth. It applied Halliday Systemic Functional Grammar to pinpoint and analyze the occurrences of processes in the poetry. There are five poetry which is taken as the subject on this research. The analysis is conducted based the six processes in transitivity system. The analysis found that there are five processes coded in the poetry of William Wordsworth. They are material, mental, relational, behavioral and existential. It also resulted that the most dominant types is the material process. It’s meant that poetry tells about the poet’s action in expressing of his idea, feeling and showing in life. This finding also shows that William Wordsworth as the poet uses the material process to build the imagery such as personification, simile and metaphor. Related to the findings of this study, the application of analysis experiential meaning can be implicated in writing and reading academic as well as translators, students and instructors involved in writing and reading pedagogy.